Examining the Challenges in the Implementation of Upper Basic Curriculum in Nigeria - Samuel, A. B. (Kashere Journal of Education, 2021)
This study sought to examine the relevance of curriculum as the foundation of education at the upper basic level in Nigeria: challenges and way forward. Three research questions and three hypotheses were generated to guide this study. The study adopted a descriptive survey design. The target population for this study was 4361 respondents made up of 66 principals and 4295 teachers from the 66 public secondary schools in Gombe State. Sample for this study was 44 principals and 200 teachers selected from public secondary schools in Gombe state of Nigeria. A structured questionnaire was used as an instrument for data collection. The data collected were analyzed using mean and standard deviation. The null hypotheses were tested at 0.05 level of significance using t-test. The findings of this study showed that the relevance of curriculum as the foundation of education at the upper basic level are that it boosts the reputation of schools, enhance upper basic education, determines the principles and procedures which will help educators in selecting and arranging instructional programmes, helps in the realization of educational objectives, helps teachers and instructors deliver quality content that is properly arranged among others. The findings of the study disclosed that the challenges of curriculum as the foundation of education at the upper basic level include inadequate planning and implementation of the curriculum, non-involvement of teachers in the planning stage of the curriculum, non-payment of teachers’ salaries and other incentives, inadequate supply of human and materials resources in the school among others. The findings of the study unveiled that the way forward to the challenges of curriculum as the foundation of education at the upper basic level include adequate planning and implementation of the curriculum, teacher’s involvement in the planning stage of the curriculum, regular payment of teachers’ salaries and other incentives, adequate supply of human and materials resources in the school among others. The study recommended that the government should ensure better conditions of service, remuneration, job mobility and promotion for teachers. The government must ensure better funding of education to guarantee adequate infrastructure, school materials, supply of equipment to the laboratories and workshops.